ANALISIS PERBEDAAN PENGATURAN ANTARA UNDANG - UNDANG NOMOR 13 TAHUN 2016 TENTANG PATEN DAN KETENTUAN TRIPs AGREEMENT TERHADAP PERJANJIAN LISENSI PATEN - Suratno, Ujang (Yustitia, 2017)
The arrangement of patent license agreements regulated in Law Number 13 of 2016 concerning Patents is the result of the ratification of the TRIPs Agreement as an Agreement on Aspects of Intellectual Property Related to Trade Policy or the Trade Related Aspects of Intellectual Property Rights. However, problems arise when the provisions of the patent license agreement regulated in Law No. 13 of 2016 concerning Patents and TRIPs Agreement have many interpretations and harm one party in their implementation. Therefore the author intends to conduct an analysis of the differences in patent license agreement arrangements in Law No. 13 of 2016 and TRIPs Agreement and the impact resulting from the different arrangements in Law No. 13 of 2016 concerning Patents with TRIPs Agreement related to patent licensing agreements. This study is a legal research using a normative juridical approach and descriptive analytical research specifications. The data used in this study are secondary data consisting of primary, secondary and tertiary legal materials. Data obtained through library studies and field research in the form of legislation, books, journals, and electronic media. The results of this study are divided into two, namely First, the factor in the differences in patent licensing arrangements in the Patent and Trips Agreement Law is the consequence of ratification which requires that international agreements be accommodated by following Indonesia's national interests and not violating the laws and regulations above. Second, the existence of two different arrangements relating to patent licensing agreements causes many interpretations in practice to lead to patent licensing agreements that contain monopolistic practices towards license recipients, so that agreements become null and void because they do not fulfil objective legal requirements, namely halal causality.